2006
DOI: 10.1074/jbc.m509500200
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Perlecan in Human Keratinocytes Reveals Novel Roles for Perlecan in Epidermal Formation

Abstract: Heparin-binding growth factors are crucial for the formation of human epidermis, but little is known about the role of heparan sulfate proteoglycans in this process. Here we investigated the role of the heparan sulfate proteoglycan, perlecan, in the formation of human epidermis, by utilizing in vitro engineered human skin. By disrupting perlecan expression either in the dermis or the epidermis, we found that epidermally derived perlecan is essential for epidermal formation. Perlecan-deficient keratinocytes for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 74 publications
2
82
0
2
Order By: Relevance
“…It is possible that G45 promotes laminin-332 deposition in SCC directly by anchoring the laminin-332 molecule to the matrix during the process of BMZ assembly. Laminin-332 G45 domain (41) has heparin-binding properties (42) and may have the ability to bind with extracellular heparan sulfate proteoglycan BMZ components, such as perlecan (43) or dystroglycan (44). However, even in the absence of G45, laminin-332 deposition was shown to be restored to near WT levels in SCC tumors through activation of the PI3K pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that G45 promotes laminin-332 deposition in SCC directly by anchoring the laminin-332 molecule to the matrix during the process of BMZ assembly. Laminin-332 G45 domain (41) has heparin-binding properties (42) and may have the ability to bind with extracellular heparan sulfate proteoglycan BMZ components, such as perlecan (43) or dystroglycan (44). However, even in the absence of G45, laminin-332 deposition was shown to be restored to near WT levels in SCC tumors through activation of the PI3K pathway.…”
Section: Discussionmentioning
confidence: 99%
“…(B and C) hSef expression pattern. Probe preparation and RNA in-situ hybridization conditions have previously been described (Sher et al, 2006). The hybridization probe spanned nucleotides 1606-2208 of the hSef common coding region (accession # AY489047).…”
Section: Resultsmentioning
confidence: 99%
“…The expression of ECM1a was found in the epidermal basal layer, in dermal blood vessels, the outer root sheath of hair follicles and in sebaceous lobules and epithelium of sweat glands, while ECM1b was expressed in the suprabasal layers of the epidermis. ECM1 is also capable of binding with perlecan, an important intrinsic molecule in skin organogenesis [8,44]. These observations suggest a crucial role for ECM1 in epidermal differentiation [5,7].…”
Section: Ecm1 Is Not Essential For Epidermal Differentiationmentioning
confidence: 77%
“…It is known that heparin-binding growth factors like perlecan are involved in organogenesis [44]. In vitro and in vivo experiments have shown that ECM1 is not essential for normal epidermal differentiation [45].…”
Section: Discussionmentioning
confidence: 99%